Pengaruh Sarcotesta dan Kadar Air Benih terhadap Kandungan Total Fenol dan Daya Simpan Benih Pepaya (Carica papaya L.) - Maryati Sari; M. R. Suhartanto; Endang Murniati (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2007)
There are phenolic compounds in sarcotesta of papaya seed which can act either as inhibitor or as antioxidant. The objective of this experiment was to study the effect of sarcotesta and seed moisture content on total phenolic content and seed longevity of papaya seed. The experiment was conducted in November 2004 - May 2005, at Bogor Agicultural University, by using papaya seed (IPB-1) harvested from Center for Tropical Fruit Studies orchard in Bogor. In this study, seeds were dried in the absence and presence of sarcotesta until 11-12% and 6-7% moisture content (mc). After drying, seeds were packed in sealed plastic bag and stored in ambient room until 0, 3, 6, 9, 12 and 15 weeks. Seed viability and total phenolic compound were evaluated every 3 weeks. Total phenolic content of seed with sarcotesta was higher (> 327mg/100g dry weight) than the seed without sarcotesta (